Designing Game For Spirituality Education At Primary School - Rico Yupita; Ridwan Sanjaya; Bernadinus Harnadi (Journal of Business and Technology, 2021)
The purpose of this research is to find out the ways to make Catholic Subject learning more enjoyable, convenient, and helpful by designing "A New Me" game that were in accordance with primary student’s necessity. This educational game was designed to teach students about the Fruit and Gifts of the Holy Spirit. The game has been examined to 50 Primary School students in age range of 10–12 years old. The subject matter used is the Fruit and Gifts of the Holy Spirit. The results of this research showned that the desire to play “A New Me” game is greatly influenced by the experience of playing digital games before, effort expectancy, enjoyment, and usability in  playing the game.